The Relationship between Economic Growth and Trade Openness: Comparison of High- and Middle-Income Countries - Almosabbeh, Imadeddin; Almoree, Mohamed (مجلة العلوم الإدارية و الإقتصادية, 2024)
The aim of this study is to test the hypothesis of nonlinearity in the relationship between the rate of trade openness and economic growth under different income conditions. This study used data for the period 1980-2020 for three groups: high-income, upper-middle-income, and lower-middle-income countries. The study also relied on the development of Khan and Senhadji (2001)model to estimate the optimum rate. This development allowed for estimating several hundreds of equations and comparing them to choose the optimum trade openness rate. The study found that the optimal rate of openness varies among different international income groups, as it is 92.9% in rich countries and 61.5% in middle-upper-income countries. It was also found that the relationship between openness and growth in rich countries is represented by a J curve, while the same relationship in upper-middle-income countries can be represented by an inverted parabola (with an extreme limit). The study recommends that middle-income countries wait to accept or be dragged behind calls for open trade as an ideal recipe for economic growth.